Technological, social and economic aspects of gold production and use by the iron age people of Southern Africa - Desai, Nirdev (Department of Archaeology, 2014)
This dissertation addresses technological, social and economIC aspects of gold production and use in the Late Iron Age of southern Africa. The topic is approached in two ways. The first is to define the fabrication technology employed in producing gold artefacts. The second is to use trace element fingerprinting to try to determine which geological deposits were exploited by gold miners of this period. Three assemblages exist that allow these questions to be addressed; Mapungubwe (1 ath - 13th century AD), Great Zimbabwe (12th - 15th century AD) and Thulamela (l4th - 17th century AD). Previous descriptions of the fabrication technology of southern African gold exist, but this is the first, systematic study of all three assemblages. The fabrication technology reconstruction used three lines of analysis; visual inspection with the naked eye, microscopy of the surfaces, and microhardness testing and metallography of selected polished samples. Fifty eight specimens were studied from Mapungubwe, two hundred and sixty eight pieces from Great Zimbabwe and fifteen from Thulamela. Trade and socio-economic effects of southern Africa's Later Iron Age are discussed in the light of the now available trace element analysis and fabrication technology of the gold artefacts studied here. No tools for working gold have been found, and inferences have been made by modelling them on tools for copper and iron working. The basic toolkit consisted of a blade, hammer, chisel, a punch and an anvil. There were four basic artefact types; wire, beads, foil and tacks. There was no significant stylistic change in artefact types and the number of artefact types in the three assemblages. Cold working and annealing were standard practices in fabrication. Ten finished artefacts types have been identified; wrapped, rolled and punched beads, foil, strips cut from foil, tacks, straight and coiled wire, rod sections and links. Other gold artefacts were recovered but were either offeuts or in the process of being made into one of the ten types described above. These are prills, discs and offcuts. Trace element groups were based on grouping the samples by similarities in the signature profiles. Identification was on the basis of the presence and absence of metallic impurities. It was deduced that alluvial gold mining was practised alongside reef gold mining. Mixing of gold ores occurred. Alloying was not intentionally practised. Identification of the gold sources would require further analysis of unworked material from potential geological sources.